2016
DOI: 10.1021/acs.jafc.6b01158
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Cysteine Adducts of Deoxynivalenol

Abstract: Conjugation with the biologically relevant thiol glutathione is one of the metabolic pathways for the mycotoxin deoxynivalenol (DON) in wheat. The occurrence of putative DON-cysteine conjugates has also been shown in wheat, likely in part as a result of degradation of the glutathione conjugates. It was reported that thiols react in vitro with DON at two positions: reversibly at C-10 of the α,β-unsaturated ketone and irreversibly at C-13 of the epoxy group. We synthesized pure DON-cysteine adducts and made anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
49
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(63 citation statements)
references
References 22 publications
14
49
0
Order By: Relevance
“…The type of conjugate present in the extract corresponded to a kinetically favored, and thus relatively fast-forming, isomer (see chromatogram 1 for DON–GSH, –CysGly, and –Cys in Figure 2) from Michael addition at C-10 (Figure 1). It has been shown that this initial product from the reaction of DON with mercaptoethanol, Cys or GSH is replaced (under neutral or mildly basic reaction conditions) by other C-10 conjugates and a C-13 conjugate over time [6,7,8], and the same occurred in the present study during conjugation with GSH, CysGly, Cys (Figure 2), γ-GluCys and N -acetylcysteine (NAC) (Figure S1). …”
Section: Resultssupporting
confidence: 75%
See 4 more Smart Citations
“…The type of conjugate present in the extract corresponded to a kinetically favored, and thus relatively fast-forming, isomer (see chromatogram 1 for DON–GSH, –CysGly, and –Cys in Figure 2) from Michael addition at C-10 (Figure 1). It has been shown that this initial product from the reaction of DON with mercaptoethanol, Cys or GSH is replaced (under neutral or mildly basic reaction conditions) by other C-10 conjugates and a C-13 conjugate over time [6,7,8], and the same occurred in the present study during conjugation with GSH, CysGly, Cys (Figure 2), γ-GluCys and N -acetylcysteine (NAC) (Figure S1). …”
Section: Resultssupporting
confidence: 75%
“…This finding was verified by HRMS/MS targeting the [M − H] − ions of DON–GSH (Figure 3). We previously reported that MS-fragmentation of the [M − H] − ions of DON–thiol conjugates is well suited to distinguishing between the products from Michael addition to C-10 and addition to the epoxide at C-13 [6,7]. Thus, fragmentation of the C-10 conjugates yielded primarily negatively charged amino acid or peptide fragments, while fragmentation of the C-13 conjugates gave product ions primarily related to the trichothecene moiety [6,7].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations